AWARENESS-IN-ACTION: A Critical Integralism for the Challenges of Our Times. - O'Connor, Daniel J. (Journal of Integral Theory & Practice, 2013)
Awareness-in-Action is a critical integral meta-paradigm that is grounded in what appear to be the presupposed perspectives and practices of human awareness-in-action in all its myriad forms, inclusive of anything and everything people do, regardless of how purposeful or spontaneous, mental or physical, independent or interdependent these actions-in-awareness might seem. To whatever extent these apparent presuppositions might be regarded as provisionally valid, these would logically serve as necessary premises for all disciplined inquiries into, and hypotheses about, the many fields of human awareness-in-action, from politics and governance to economics and business to sociology and social work to journalism and activism. Awareness-in-Action may therefore provide the meta-paradigmatic means to create actionable knowledge within, across, and beyond established disciplinary and institutional boundaries, so that those of us concerned with such matters might learn how to respond more effectively to the interdependent political, economic, social, and ecological challenges of our time. This article summarizes the primary features of Awareness-in-Action before elaborating on some of its philosophical implications rooted in Jürgen Habermas's critical theory, Ken Wilber's Integral Theory, and Chris Argyris's action science.